KONTRIBUSI MASYARAKAT DALAM MENENTUKAN ARAH PEMBANGUNAN EKONOMI GLOBAL YANG BERKELANJUTAN DI INDONESIA - Seli Yulia; Endang Supriatna (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Indonesia has an important role in terms of community contribution in determining the direction of sustainable global economic development. The method used in writing this journal is a literature review or literature study. However, the community's contribution to the global economic development process in Indonesia is still relatively low. This is caused by various factors, such as lack of access to information and community participation, weak institutional capacity, lack of trust in the government, lack of awareness of sustainable development, and weak coordination and cooperation. Therefore, the aim of this research is to explore how society can contribute in determining the direction of sustainable global economic development in Indonesia. This method was chosen because society's contribution to economic development is still often ignored, even though society has a large role in creating policies that support sustainable economy. To overcome this, there is a need to increase awareness, strengthen the capacity of civil society, and increase cooperation between stakeholders. Therefore, sustainable economic development is an important goal for Indonesia in the current global context. To achieve this goal, community contributions are very necessary so that development can run inclusively, fairly and benefit all levels of society.